PENGEMBANGAN e- MODUL TEMATIK UNTUK PEMBELAJARAN KELAS IV SEKOLAH DASAR - Indra Indra; Indri Astuti; Aloysius Mering (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
ABSTRACTThis study aims to develop a thematic e-module for class IV Elementary Schoolstudent learning. The e-Module development uses the research and developmentmethod of the Dick and Carey product development design model. Data obtainedthrough conservation activities, interviews and documentation. The results of thestudy are in the form of thematic e-Module development products. The thematic e-Module products have been validated by three experts, the three experts gave agood value which means that the product was suitable for use in the field. Based onfield trials namely one-to-one trials, small group trials, and large group trials alsoget a positive response that the e-Module product felt a change in learningactivities. the main field trials obtained the following results, the pretest resultsobtained an average of 51.59 then 73.87 posttest results and after calculated withthe t test, the results obtained, t count 21, 593 and t table 0,000 because t count isgreater than t table, then there are differences from before and after the use of e-Modules. based on these calculations it can be concluded that the e-thematicModule is effectively used as teaching material.Keywords: e-Module, Thematic